Biomass gasification in the bioethanol production - Boiko, Petro; Bondar, Nikolai; Kuts, Anatoly (My University, 2018)
Монография содержит научные исследования авторов в области техники и технологий. Может быть полезна для инженеров, руководителей и других работников предприятий и организаций, а также преподавателей, соискателей, аспирантов, магистрантов и студентов высших учебных заведений. The monograph contains the scientific research of the authors in the field of engineering and technology. It can be useful for engineers, managers and other employees of enterprises and organizations, as well as teachers, applicants, graduate students, undergraduates and students of higher educational institutions.
Keywords: біоетанол; bioethanol; газифікація; gasification; кафедра біотехнології продуктів бродіння і виноробства